2020
DOI: 10.1093/biolinnean/blaa009
|View full text |Cite
|
Sign up to set email alerts
|

Much more than a clasp: evolutionary patterns of amplexus diversity in anurans

Abstract: The evolution and diversification of animal reproductive modes have been pivotal questions in behavioural ecology. Amphibians present the highest diversity of reproductive modes among vertebrates, involving various behavioural, physiological and morphological traits. One such feature is the amplexus, which is the clasp or embrace of males on females during reproduction and is found almost universally in anurans. Hypotheses about the origin of amplexus are limited and have not been tested thoroughly, nor have t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 70 publications
(59 reference statements)
1
27
0
Order By: Relevance
“…The inguinal amplexus mode that we documented in P. magnapustulosus and P. myanhessei is supported as an autapomorphy of the genus Phrynoglossus by the observation of an inguinal amplexus mode also in P. sumatranus by Eto and Matsui (2012). According to a large-scale analysis of the amplexus mode across all groups of anuran amphibians, reveal the inguinal amplexus as the basal state to all Anura (Carvajal-Castro et al 2020). However, the latter authors gave the axillary amplexus as the only mode found within the family Dicroglossidae obviously not being aware of the inguinal amplexus mode in Phrynoglossus.…”
Section: Discussionsupporting
confidence: 65%
“…The inguinal amplexus mode that we documented in P. magnapustulosus and P. myanhessei is supported as an autapomorphy of the genus Phrynoglossus by the observation of an inguinal amplexus mode also in P. sumatranus by Eto and Matsui (2012). According to a large-scale analysis of the amplexus mode across all groups of anuran amphibians, reveal the inguinal amplexus as the basal state to all Anura (Carvajal-Castro et al 2020). However, the latter authors gave the axillary amplexus as the only mode found within the family Dicroglossidae obviously not being aware of the inguinal amplexus mode in Phrynoglossus.…”
Section: Discussionsupporting
confidence: 65%
“…We were unable to determine the function of this novel reproductive behavior exhibited by Lau’s leaf litter toad. This period of amplexus could be part of courtship (e.g., Carvajal‐Castro et al 2020), a signal by the female that she will mate with the male, which is then followed by another form of amplexus during oviposition and fertilization. This is not an unlikely scenario, as other species of frogs engage in different forms of amplexus prior to and during oviposition (e.g., Pombal et al 1994, Bourne et al 2001, Willaert et al 2016).…”
Section: Discussionmentioning
confidence: 99%
“…Diversity in amplexus has foundations in phylogeny and the environment, with axillary and inguinal amplexus being the two most common forms (Carvajal‐Castro et al 2020). Inguinal amplexus, in which the male grasps the female around the waist, is considered the ancestral condition.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Fertilization in Anura mainly occurs externally, taking place by amplexus, involving the male grasping the female with its front legs and covering the eggs with sperm as they are released from the female's body [51]. After fertilization, the life cycle of most anurans starts in water when the eggs hatch into limbless larvae with gills.…”
Section: Anura Generalities About Anuramentioning
confidence: 99%